Maternal Vitamin D Status and Its Effect on Vitamin D Levels in Early Infancy in a Tertiary Care Centre in Sri Lanka - Kaneshapillai Anusha; Usha Hettiaratchi; Dulani Gunasekera; Shamini Prathapan; Guwani Liyanage (International Journal of Endocrinology)
Epidemiologic studies from South Asian countries have reported vitamin D deficiency among all age groups. However, there is very little information on vitamin D levels, especially in the vulnerable populations (pregnant/breast feeding mother and infants) in Sri Lanka. More data on vitamin D status of such populations will be important for policy decisions to be made at a national level. Similarly, it will be valuable for healthcare programs in other countries (e.g., United States, Australia, Europe, and Canada) as Sri Lankans are a fast-growing migrant population to those countries. The purpose of this study was to investigate maternal vitamin D status and its effects on infants in a state sector tertiary care centre in Sri Lanka. This prospective cohort study was conducted on 140 healthy pregnant mothers in the third trimester (mean gestational age 39±1 weeks). Blood was collected for 25(OH)D and parathyroid hormone (PTH). Sun exposure and feeding patterns of the infants were recorded based on maternal reporting. Mean age of the infants at follow-up visit was 36±7 days. Vitamin D (25 (OH)D) deficiency (<25 nmol/L) was observed in 12% pregnant mothers, 5% lactating mothers, and 63% infants. Insufficiency (<50 nmol/L) was found in an additional 51% and 43% in pregnant and lactating mothers and 25% of infants. Mean 25(OH)D was higher in pregnant (46.4±17.5 nmol/L) and lactating (51.9±17.0 nmol/L) mothers than infants (28.1±13.7 nmol/L). Maternal vitamin D level during pregnancy was a significant risk factor (OR: 6.00, 95%CI: 1.522-23.655) for infant deficiency and insufficiency. Sun exposure of infants showed a significant positive correlation with vitamin D level (OR: 3.23, 95%CI: 1.19-8.68). In conclusion, the presence of Vitamin D deficiency/insufficiency is higher in infants compared to pregnant/lactating mothers. Low maternal 25(OH)D during pregnancy was a risk factor for deficiency in infants. Although majority of lactating mothers had sufficient vitamin D, most of their exclusively breastfed offspring were deficient.